Desafios para a organização social dos catadores de materiais reutilizáveis e recicláveis em Itabaianinha-SE - Santos, Cyntia Sena (2020)
Waste pickers of reusable and recyclable materials are considered as one of the vulnerable social groups that find in the collection of discarded materials by society the basis of income and sustenance of their families. This research aimed to analyze the working conditions and challenges faced by the social organization of waste pickers in Itabaianinha-SE. These collectors have great importance as environmental agents, because they also contribute to urban cleaning and minimizing social and environmental impacts. The cooperatives and associations are among the main instruments of social insertion of the collectors, because they provide advantages and better working conditions for these citizens. The method used was the hypothetical-deductive with quality-quantitative bias and as methodological procedures: bibliographic and documentary survey; field research based on interviews with collectors associated to the cooperative and with those who perform the collection of recyclable materials in an informal way; field research based on systematic observation and photographic records; Rapid and Participatory Diagnosis (RDRP); tabulation, analysis and interpretation of information. The research was conducted with 18 collectors of recyclable and reusable materials from the city of Itabaianinha-SE, 13 of them are in the Cooperative COORSITA, and 05 perform their work activities in the municipal dump. The survey identified that 78% of the interviewed collectors are male, who have a greater workload in relation to women (22%), the level of schooling is relatively low due to socioeconomic factors, they live in areas considered of low purchasing power, with a monthly income below a minimum wage. Waste pickers work in unhealthy conditions, with excessive working hours, without rest, exposed to risks of accidents and illness due to exposure to the sun, rain, bad smell and lack of Personal Protective Equipment (PPE). These workers survive without social recognition and appreciation, in addition to living with daily prejudices due to their function. The devaluation and ignorance on the part of Brazilian society is still one of the bottlenecks to be overcome in the profession and in the daily life of these vulnerable groups. The search for partnerships with public and private agencies is primordial, especially in what concerns professional qualification, support for the social insertion of cooperative and informal workers and for the recognition of the category of workers and their importance to society and the environment. It is through social organization that these workers can fight for strengthening in the search for better working conditions, social insertion and quality of life. The insertion of public policies by the competent agencies is of paramount importance so that they make it possible for waste pickers to acquire knowledge about their importance in the solid waste management system, especially in the selective collection and recycling cycle of recyclable materials.